Performance cost index in evaluating oil palm stem as alternative fibre material in chain of custody certification of plywood mills in Malaysia - Adnan, Aida (2018)
The major concern in chain of custody (COC) certification is the cost of implementation and maintenance. Thus, the main aim of this study is to assess the above said costs and factors that motivate the Malaysian certified plywood mills. First stage of the study was the identification of motivational factors. Second was evaluations of COC cost components where, certified plywood mills in Malaysia were surveyed through personal interview. The independent variables were measured using Likert-like scale. The third stage was an application of performance cost index (PCI). Mann-Whitney, percentage data analysis and regression with an econometric analysis were used to analyse data on motivational factors. Data collected on cost components was analysed using simple mean and one-way ANOVA. Pearson’s correlation analysis was used to explore the relationship between grades of plywood product and PCI, as well as PCI and plywood price. Whilst, linear regression analysis was used to predict the new plywood product price. Result of the study shows that seven cost components were identified in COC certification; 1) cost of procuring certified raw material (MYR1.24/m³ to MYR2.44/m³); 2) consultancy (plus training) MYR0.41/m³ to MYR0.47/m³); 3) auditing fees (MYR0.99/m³ to MYR1.59/m³); 4) documentation (MYR0.04/m³ to MYR0.27/m³); 5) marketing or promotional (MYR0.35/m³ to MYR0.49/m³); 6) continuous training (MYR0.00/m³ to MYR0.21/m³) and 7) cost for hiring additional staff or reward given (MYR0.00/m³ to MYR0.06/m³). 41% of the certification cost was due to certified raw material which is statistically significant at P≤0.05. Thus, as an alternative, Oil Palm Stem (OPS) was introduced. The study proposed a “Performance Cost Index (PCI)” to be used as a guiding tool in consuming OPS as raw material. PCI has shown as a good predictor for plywood grade (R² = 0.50) and price (R² = 0.70). In term of performance value over cost (PCI), OPS give better PCI results than using MLHW (1.57). Plywood produced using 100% OPS through improved production method shows the best result (1.82) followed by OPS mixed plywood (1.76) produced through conventional method. Every change in PCI will result in a marginal change on average of 555.91 unit of plywood cost.